2014
DOI: 10.1152/jn.00140.2013
|View full text |Cite
|
Sign up to set email alerts
|

Haptic feedback enhances rhythmic motor control by reducing variability, not improving convergence rate

Abstract: Stability and performance during rhythmic motor behaviors such as locomotion are critical for survival across taxa: falling down would bode well for neither cheetah nor gazelle. Little is known about how haptic feedback, particularly during discrete events such as the heel-strike event during walking, enhances rhythmic behavior. To determine the effect of haptic cues on rhythmic motor performance, we investigated a virtual paddle juggling behavior, analogous to bouncing a table tennis ball on a paddle. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 81 publications
3
39
0
Order By: Relevance
“…Prior studies on ball bouncing have also demonstrated the importance of ball-racket impact in behavior. For instance, in contrast to haptic guidance throughout the entire racket trajectory, haptic feedback at the ball-racket impact does improve performance and learning (Sternad et al 2001; Ankarali et al 2014). An intervention that focuses on physical contacts has also been shown a promising direction for robotic assistance in locomotor recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on ball bouncing have also demonstrated the importance of ball-racket impact in behavior. For instance, in contrast to haptic guidance throughout the entire racket trajectory, haptic feedback at the ball-racket impact does improve performance and learning (Sternad et al 2001; Ankarali et al 2014). An intervention that focuses on physical contacts has also been shown a promising direction for robotic assistance in locomotor recovery.…”
Section: Discussionmentioning
confidence: 99%
“…, t n−1 , such that t 0 < t 1 < · · · < t n . Each event time corresponds to a hybrid transition, giving rise to a sequence of discrete states α 0 , · · · , α n−1 and smooth trajectories q αi (t) ∈ V αi , t ∈ [t i , t i+1 ], such that each q αi is a trajectory of the continuoustime dynamical system on V αi given in (2). Further, the…”
Section: Hybrid Dynamical System Formulation With Exogenous Inputmentioning
confidence: 99%
“…Rhythmic dynamic behaviors can be observed in a wide variety of biological and robotics systems, such as terrestrial locomotion [3,17] and juggling [2,4]. Such behaviors often include hybrid characteristics in that they exhibit both smooth flows punctuated by discrete jumps and are often modeled as hybrid dynamical systems [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, visual and haptic feedback can improve performance of lower extremity training than visual-only and haptic only mode [8]. Cowan et al have shown that providing sensory feedback-like force impulse to the hand while performing rhythmic motor tasks, such as virtual paddle juggling, enhances performance by reducing variability in the rhythmic movement [9].…”
Section: Introductionmentioning
confidence: 99%